2021
DOI: 10.11137/1982-3908_2021_44_36119
|View full text |Cite
|
Sign up to set email alerts
|

Análise Espaço-Temporal de Áreas de Queimadas no Estado do Maranhão a partir de Imagens MODIS e Classificação Random Forest

Abstract: O mapeamento de áreas queimadas através de imagens de sensoriamento remoto apresenta uma série de questões importantes no gerenciamento espacial de estudos de detecção de focos de calor, análise de risco de incêndio, avaliação de danos e gerenciamento de processos de regeneração florestal. Neste estudo foi apresentada uma abordagem metodológica para mapeamento de áreas de queimadas no estado do Maranhão de 2001 a 2019 a partir de dados do satélite Terra/MODIS e do Algoritmo de Classificação Binária Random Fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Santana et al [88], using MODIS images and its derived products in all Brazilian biomes, found a CE of 42.01% and an OE of 78.03%. Pacheco and Silva Júnior [89] obtained, in the state of Maranhão, OE and CE values of approximately 80%. Franquesa et al [90] obtained an estimated CE and OE of 19% and 49%, respectively using MODIS MCD64 data, while Katagis and Gitas [91] obtained greater OE (52%) but lower CE (19%) than FireCCI51 (OE = 0.36 and CE = 0.40) in Mediterranean ecosystems.…”
Section: Analysis Of Detection Errors and Relationship With Other Stu...mentioning
confidence: 93%
“…Santana et al [88], using MODIS images and its derived products in all Brazilian biomes, found a CE of 42.01% and an OE of 78.03%. Pacheco and Silva Júnior [89] obtained, in the state of Maranhão, OE and CE values of approximately 80%. Franquesa et al [90] obtained an estimated CE and OE of 19% and 49%, respectively using MODIS MCD64 data, while Katagis and Gitas [91] obtained greater OE (52%) but lower CE (19%) than FireCCI51 (OE = 0.36 and CE = 0.40) in Mediterranean ecosystems.…”
Section: Analysis Of Detection Errors and Relationship With Other Stu...mentioning
confidence: 93%